Vertical and Horizontal Integration in the Profitability of Malaysian Broiler Firms - Y. S. Tey; P. Arsil (Faculty of Animal Science, Bogor Agricultural University, 2021)
Vertical integration has been widely promoted for offering production, transaction, and market benefits in the poultry industry. These benefits must be translated into profitability – a proxy of competitive advantage. This study aimed to identify the financial effect underlying the degree of backward, forward, and horizontal integration, alongside the financial strength and management capability of broiler firms. We used random-effects general least squares to analyze a panel dataset of broiler firms that publicly listed in Kuala Lumpur Stock Exchange Malaysia for the 2006-2018 period. Support is found for the hypothesis that forward integration enhanced profitability. In comparison, the operating margin had a greater influence on broiler firms’ financial performance. Notwithstanding value chain development, the relative findings suggest that efficiency remains a priority in a commodity-based broiler market. It is thus recommended that management capability be emphasized.